IMPROVING THE STUDENTS’ SPEAKING ACCURACY THROUGH “LSE 9.0 SOFTWARE VERSION” - Firman Firman; Muhammad Zia ul Haq (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2012)
The objective of the research was to find out the improvement students’ speaking accuracy through Learn to Speak English 9.0 Software Version at SMK Negeri 1 Pattallassang Gowa. This research used classroom action research that consists two cycles. The research object was the first year electric students’ of SMK Negeri 1 Pattallassang Gowa academic year 2011/2012. The object of this research consisted of 32 students. The researcher obtained the data by using the speaking test in the diagnostic test, the cycle I and Cycle II. The results of the student's speaking test in cycle I and cycle II had significantly different scores.  There was a better improvement of gains by students at the end of action cycle II. The research findings indicated that use of Learn to Speak English 9.0 Software as teaching media could improve the students’ speaking accuracy after evaluation in cycles I and II, the means scores in diagnostic test is 5.21 and then it became 5.95 in the cycle I and 7.10 in the cycle II. It can be stated that the students’ speaking accuracy at the first year electric students’ of SMK Negeri 1 Pattallassang Gowa was in poor level after the test in the diagnostic test with mean score 5.21 had improved to fairly good level after the test in the cycle II with mean score 7.10.Keyword: Speaking, accuracy, LSE 9.0 software version